Formulation Of Ajatulama Hand Soap Preparation Against The Decline Of Microorganisms - Syafruddin Ali Salaka; Iqra S (Midwifery and Nursing Research, 2022)
Background: Human hands are often the agents that carry germs and cause pathogens to pass from one person or from nature to another through direct or indirect contact. Washing hands with water alone is more common, but it has proven to be ineffective in maintaining health compared to washing hands with soap. One of the plants that contain one or more active ingredients that can be used as an antibacterial is a plant. Turi leaves contain flavonoids, alkaloids, saponins, and tannins which have been shown to have antibacterial effects against Staphylococcus aureus and Candida sp. Turi leaf extract (Sesbania grandiflora Pers.) has antibacterial activity against Escherichia coli, Bacillus subtilus, Staphylococcus aureus, Pseudomonas aeruginosa, especially against Escherichia coli and Pseudomonas aeruginosa. Methods: This research is a quasi-experimental research (quasi-experimental). The research design used was, one group pre-post test design, namely experimental research carried out in only one group called the experimental group without any comparison group or control group. The research was carried out at the Poltekkes Campus Laboratory of the Ministry of Health, Mamuju. The instruments used consist of tools and materials to mix turi leaves with atanol. Results: 4% concentration experienced a significant decrease in microorganisms. before examining the number of microorganisms 34,000 and after examining the number of microorganisms 3,000 with a difference of 31,000 microorganisms. Concentration of 8% turi leaf extract with 70% ethanol decreased microorganisms. before checking the number of microorganisms 12,100 and after examining the number of microorganisms 4,066 with a difference of 8034 microorganisms. Concentration of 12% turi leaf extract with 70% ethanol decreased microorganisms. before checking the number of microorganisms 7,766 and after examining the number of microorganisms 3,733 with a difference of 4,033 microorganisms. Conclusion: Turi leaf extract hand soap with 70% ethanol is more effective in killing microorganisms